En verden Hinsides - Jørgensen, Jens Lohfert (Academic Quarter | Akademisk kvarter, 2015)
This article deals with the Danish author Helga Johansen’s autobiographical novel Hinsides (1900) as an example of a distinctive body of works written around the turn of the century that deal with mental disorder. The article consists of two main parts. In the first, a short reflection of the genre of the so-called pathography is followed by a longer discussion of the relationship between gender, mental disorder and writing around the turn of the century. The second part deals with Hinsides, focusing on the way in which the experience of being ill is produced by the novel, and on the pressure put on language in this process.